Impact of healthcare services on thyroid cancer incidence among World Trade Center‐exposed rescue and recovery workers. Issue 10 (18th July 2021) - Goldfarb, David G.; Colbeth, Hilary L.; Skerker, Molly; Webber, Mayris P.; Prezant, David J.; Dasaro, Christopher R.; Todd, Andrew C.; Kristjansson, Dana; Li, Jiehui; Brackbill, Robert M.; Farfel, Mark R.; Cone, James E.; et al.
Abstract: Background: A recent study of World Trade Center (WTC)‐exposed firefighters and emergency medical service workers demonstrated that elevated thyroid cancer incidence may be attributable to frequent medical testing, resulting in the identification of asymptomatic tumors. We expand on that study by comparing the incidence of thyroid cancer among three groups: WTC‐exposed rescue/recovery workers enrolled in a New York State (NYS) WTC‐medical monitoring and treatment program (MMTP); WTC‐exposed rescue/recovery workers not enrolled in an MMTP (non‐MMTP); and the NYS population. Methods: Person‐time began on 9/12/2001 or at enrollment in a WTC cohort and ended at death or on 12/31/2015. Cancer data were obtained through linkages with 13 state cancer registries. We used Poisson regression to estimate rate ratios (RRs) and 95% confidence intervals (CIs) for MMTP and non‐MMTP participants. NYS rates were used as the reference. To estimate potential changes over time in WTC‐associated risk, change points in RRs were estimated using profile likelihood. Results: The thyroid cancer incidence rate among MMTP participants was more than twice that of NYS population rates (RR = 2.31; 95% CI = 2.00–2.68). Non‐MMTP participants had a risk similar to NYS (RR = 0.96; 95% CI = 0.72–1.28). We observed no change points in the follow‐up period. Conclusion: Our findings support the hypothesis that no‐cost screening (a benefit provided by WTC‐MMTPs) is associated with elevated identification of thyroid cancer. Given the high survival rate for thyroid cancer, it is important to weigh the costs and benefits of treatment, as many of these cancers were asymptomatic and may have been detected incidentally.